Linear Paul trap design for high-fidelity, scalable quantum information processing - Woodrow, S (2016)
We have designed and built a new linear Paul trap to expand our capability for carrying out high-fidelity quantum logic. We have identified some key limitations of our existing trap: the presence of a magnetic field gradient of 0.6 milligauss per micrometre, which limits the fidelity of Bell state preparation; a high axial micromotion amplitude, which limits the fidelity of operations on linear ion crystals; and a small numerical aperture in the imaging system, which restricts the collection efficiency and thus the performance of remote entanglement experiments. We have carried out theoretical investigations into axial ion micromotion, including a full analysis of ion motion, using numerical simulations to understand the impact of electrode geometry. We have considered the effect of ion micromotion on the excitation spectrum, and how the micromotion sidebands can be used to selectively address ions within a linear crystal. Based on this work, electrode design parameters have been selected for the new trap to prioritise sideband addressing while maintaining the most useful properties of the existing design. We have redesigned the mechanical structure of the trap, carefully considering manufacturing limitations, to minimise the magnetic field gradient, increase the numerical aperture to 0.6 and accurately align the electrodes. Additionally, we have considered methods of characterising the trap performance to assess how well the design criteria have been met.